An Ounce of Prevention for a Pound of Cure: Efficiency of Community-Based Healthcare - Antonella Bancalari; Pedro Bernal; Pablo Celhay; Sebastian Martinez; Maria Deni Sánchez (Institute of Labor Economics (IZA), 2023)
We study the efficiency in health systems generated by community health teams, a common strategy in low- and middle-income countries for primary healthcare delivery. We exploit the rollout of a nation-wide expansion of coverage to this model in El Salvador. Using a panel dataset of municipalities spanning 2009-2018 from consultation and hospital records of almost 4 million episodes, we show that investing in community-based healthcare, which relied on less-specialized health workers, led to a more efficient allocation of care. Preventive care increased and curative care and hospitalizations from preventable conditions decreased, while coverage in curative care for previously unattended chronic diseases increased.
Keywords: I15; I18; H21; H51; 330; community-based healthcare; efficiency; access